How do you work x=2y-2 and 3y=x+6 as substitution?

3 Answers
Apr 13, 2018

=>x = 6
=>y = 4

Explanation:

Substitution involves putting a known variable expression into another expression.

In this case, you are given x = 2y-2. You can substitute this into the second equation as follows:

=>3y = x+6

=>3y = (2y-2) + 6

=>3y = 2y + 4

=>y = 4

Now, you can use this y = 4 to find the value of x. Going back to our expression for x:

=>x = 2y - 2

=>x = 2(4) -2

=>x = 8 - 2

=>x = 6

So the solution is x = 6 and y = 4.

Apr 13, 2018

y=4
x=6

Explanation:

x=2y-2
3y=x+6

The first one will be easiest to plug into the second, since it is already defined for x. So, we will be substituting the x in the second equation with the definition of x provided in the first.

3y=(2y-2)+6

The parenthesis do not prevent you from combining like terms. In this case, the -2 and 6.

3y=2y+4

3y-2y=4

y=4

Now plug the y in to the top problem to solve for x.

x=2(4)-2

x=6

Results: y=4 and x=6

Apr 13, 2018

x=6
y=4

Explanation:

x=2y-2
3y=x+6

To solve for each variable through substitution we have to make one equation have only one variable in it (either x or y). In order to do this, we have to put one variable in terms of the other. This time we got lucky because the first equation already puts x in terms of y. We just have to plug in 2y-2 for x in the second equation.

3y=x+6

3y=(2y-2)+6

3y=2y+4

Subtract 2y from each side

y=4

Now plug this value into one of the original equations to find x.

x=2y-2

x=2(4)-2

x=8-2

x=6

OR

3y=x+6

3(4)=x+6

12=x+6

6=x

Answer

x=6
y=4